Laser cladding titanium-based composite coating on surface of titanium alloy drill rod and preparation method of laser cladding titanium-based composite coating
By using spherical TC4-TiBw or TC4-TiC composite powder for laser cladding technology, the problem of easily defects in the cladding process of titanium-based composite coating is solved, and high-quality titanium-based composite coating preparation is achieved, which improves the hardness and wear resistance of titanium alloy drill rods, extends its life and reduces costs.
Patent Information
- Application Number
- CN202510118988.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
AI Technical Summary
The existing titanium-based composite coatings are prone to defects during the cladding process, resulting in poor coating quality.
Spherical TC4-TiBw or TC4-TiC composite powder is used as raw materials, and a titanium-based composite coating is formed on the surface of the titanium alloy drill rod through laser cladding technology. The rapid cooling characteristics of laser cladding are used to avoid the coarseness of the nano-reinforced phase and the growth of matrix grains.
The high-quality preparation of titanium-based composite coating is achieved. The coating is well-combined with the substrate metallurgy, and the surface hardness and wear resistance are better than the substrate, which extends the life of the titanium alloy drill rod and reduces production and maintenance costs.
Smart Images

Figure CN119876939A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser additive manufacturing, and specifically relates to a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod and a preparation method thereof. Background Art
[0002] With the development of the world economy, the demand for oil and natural gas continues to grow. At present, large-scale international oil and gas development projects are concentrated in the fields of deep wells, ultra-deep wells, deep sea wells, and highly corrosive wells, and the difficulty of drilling oil and gas wells has increased significantly. This shows that only by continuously researching and developing new drill pipe products that meet the latest drilling technology requirements can we meet the increasingly demanding drilling operation requirements. Compared with steel materials, titanium alloys have low density, high specific strength, excellent corrosion resistance, good medium and high temperature mechanical properties, excellent fatigue resistance and creep resistance, and the manufacturing process of titanium alloy pipes is mature. At present, the most widely used titanium alloy oil pipe is Ti-6Al-4V, but its high cost and poor wear resistance limit its application in the field of oil pipes.
[0003] At present, the main way to reduce the cost of titanium alloy materials and their forming technology is to use cheap elements to design alloy components. That is, when designing titanium alloy materials, cheap elements such as Fe, Si, Al, Sn are used to replace expensive elements such as V, Mo, Zr, Nb, Ta, etc. ATI425 titanium alloy is a new type of low-cost α+β two-phase titanium alloy developed based on the above idea, using cheap Fe elements to replace the expensive V element in the raw materials of Ti-6Al-4V alloy. The strength is equivalent to that of TC4 alloy, which greatly reduces the production cost.
[0004] In order to improve the wear resistance of titanium alloy materials, titanium alloys are usually surface modified. Laser cladding technology uses high-energy laser as a heat source to melt the cladding material and the substrate surface, and after cooling, a coating that enhances the surface properties of the substrate material is formed. It has the characteristics of high power, high efficiency, high metallurgical bonding, etc., and can repair damaged parts, extend service life, and reduce costs. Therefore, it is mainly used to improve and repair the wear resistance of titanium alloy materials.
[0005] Cladding materials mainly include alloy powder, ceramic powder, and metal-based ceramic composite powder. Among them, metal-based ceramic powder has the advantages of good metal toughness and strong ceramic wear resistance, so it has the best comprehensive performance and is the current research hotspot. Common reinforcing phases in titanium-based composite materials include TiB, SiC, TiC, TiB2, and B4C. Among them, TiB has a high elastic modulus (about 450-550 GPa), good interface bonding with the matrix, and a thermal expansion coefficient similar to that of titanium alloy (TiB: 7.2×10-6 K -1 , Ti: 8.2×10-6 K -1) and other characteristics, which can reduce the residual stress in the coating and prevent the coating from cracking, and is an ideal reinforcement phase. Existing cladding powders are mostly prepared by traditional mechanical ball milling. The powder has low sphericity and poor fluidity, which will lead to defects in the cladding process of titanium-based composite coatings and poor quality of the cladding layer. Summary of the invention
[0006] The purpose of the present invention is to provide a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod and a preparation method thereof, so as to solve the technical problem that defects are easily generated in the existing cladding titanium-based composite coating process.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod, comprising the following steps: The surface of the pretreated titanium alloy drill pipe is subjected to laser cladding using spherical titanium-based composite powder as a raw material to form a titanium-based cladding layer on the surface of the titanium alloy drill pipe, and the titanium-based composite coating is obtained after cleaning impurities on the surface of the titanium-based cladding layer; The spherical titanium-based composite powder is a spherical TC 4 -TiBw composite powder or spherical TC 4 -TiC composite powder.
[0008] Furthermore, the spherical titanium-based composite powder is dried before use; the drying method is vacuum drying; the vacuum drying time is 4-6 h, and the vacuum degree is 0.05 MPa-0.08 MPa.
[0009] Furthermore, the method for preparing the pretreated titanium alloy drill rod is: cutting the titanium alloy drill rod to a desired size by wire cutting, and performing sandblasting.
[0010] Furthermore, the process parameters of the laser cladding are: laser power: 1000-1500W, scanning speed 8-11mm / s, spot diameter 3mm, powder feeding amount 10g / min, layer lifting 0.8mm, scanning spacing 5mm, and argon protection is used in the cladding process.
[0011] Furthermore, the particle size of the spherical titanium-based composite powder is 45-150 μm.
[0012] Furthermore, the volume fraction of the TiBw / TiC reinforcement phase in the spherical titanium-based composite powder is 1-6 wt.%.
[0013] Furthermore, the volume fraction of the TiBw reinforcement phase in the spherical titanium-based composite powder is 5.1%.
[0014] Furthermore, the material of the titanium alloy drill rod is ATI425 titanium alloy.
[0015] Furthermore, the powder feeding method of the laser cladding is coaxial powder feeding.
[0016] The invention also discloses a titanium-based composite coating prepared by the preparation method.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a laser-clad titanium-based composite coating on the surface of a titanium alloy drill rod. Spherical titanium-based composite powder containing a nano-reinforced phase (TiBw / TiC) is used as a raw material. The titanium-based composite coating is prepared on the surface of a low-cost titanium alloy through laser cladding technology. The rapid cooling characteristic of the laser cladding technology is utilized to avoid the coarsening of the nano-reinforced phase (TiBw / TiC) and the growth of matrix grains, and the strengthening effect of the nano-reinforced phase is fully exerted. At the same time, the composite powder with a quasi-continuous network distribution of the nano-reinforced phase is selected to solve the problem that defects are easily generated in the cladding layer due to the low sphericity and poor fluidity of the metal-based ceramic powder prepared by traditional mechanical ball milling.
[0018] Furthermore, the method of the present invention utilizes the rapid cooling characteristics of laser cladding technology to avoid the coarsening of the nano-reinforced phase (TiBw / TiC) and the growth of matrix grains, and gives full play to the strengthening effect of the nano-reinforced phase; the cladding layer has a good metallurgical bonding with the substrate, and the surface hardness and wear resistance are better than the substrate, thereby extending the life of the titanium alloy drill pipe.
[0019] Furthermore, the method of the present invention selects low-cost titanium alloy ATI425 with strength equivalent to TC4 as the substrate, which can greatly reduce the production cost of oil drill pipes. The laser cladding technology is simple and has high cladding efficiency, and can be used to repair titanium alloy drill pipes, thereby reducing their maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 X-ray diffraction patterns of the titanium-based composite coating and cladding raw material powder prepared in Examples 1 and 2 of the present invention; Figure 2 The scanning electron microscope images of the titanium-based composite coatings prepared in Examples 1 and 2 of the present invention; Wherein: a-Example 1; b-Example 2; Figure 3 This is a high-magnification scanning electron microscope image of the titanium-based composite coating prepared in Example 2 of the present invention; Figure 4 The side scanning electron microscope images of the fracture surface of the titanium-based composite coating prepared in Example 1 and Example 2 of the present invention in the three-point bending test; Wherein: a-Example 1; b-Example 2; Figure 5 The microhardness and macrohardness test results of the titanium-based composite coatings prepared in Examples 1 and 2 of the present invention; Where: a-microhardness; b-macrohardness; Figure 6 The wear results of the titanium-based composite coating and substrate prepared in Example 1 and Example 2 of the present invention are shown. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0022] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0023] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0024] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0025] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0026] The first aspect of the present invention provides a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod. The titanium-based composite coating having a nano-enhanced phase distributed in a quasi-continuous network has good metallurgical bonding with a substrate and also has high hardness and good wear resistance, thereby achieving a protective effect on the titanium alloy drill rod. Spherical titanium-based composite powder containing nano-reinforced phase is selected as raw material, wherein the TiBw / TiC reinforcement phase content is 1-6wt.%; The composite powder used is a spherical TC4-TiBw composite powder or a spherical TC4-TiC composite powder, which has good sphericity, uniformity and fluidity, and the nano-TiBw / TiC reinforcement phase is distributed in a network inside the powder particles; This titanium-based composite coating utilizes the rapid cooling characteristics of laser cladding technology to avoid the coarsening of the reinforcement phase and the growth of the matrix grains. The reinforcement phase is distributed in a network at the grain boundaries.
[0027] The second aspect of the present invention provides a method for preparing a laser-clad titanium-based composite coating on the surface of a titanium alloy drill pipe. The method uses spherical titanium-based composite powder containing a nano-reinforced phase (TiBw / TiC) as a raw material and uses laser cladding technology to prepare a titanium-based composite coating on the surface of a low-cost titanium alloy ATI425. The rapid cooling characteristics of the laser cladding technology can avoid the coarsening of the nano-reinforced phase (TiBw / TiC) and the growth of the matrix grains, and give full play to the strengthening effect of the nano-reinforced phase; The main steps include: Step 1, selecting TC4-TiBw composite powder as raw material; Step 2: Place the composite powder in step 1 into a vacuum drying oven and dry for 4-6 hours. The degree is 0.05 MPa-0.08 MPa; Step 3: Using ATI425 titanium alloy as the substrate, perform surface pretreatment on it.
[0028] Step 4: laser cladding the ATI425 titanium alloy after surface pretreatment to form a titanium-based composite coating on the surface. The laser cladding of the composite powder adopts a coaxial powder feeding method.
[0029] Step 5: clean the welding slag and impurities on the surface of the cladding layer to obtain a laser cladding specimen.
[0030] Preferably, the particle size of the TC4-TiB composite powder described in step 1 is selected to be 45-150 μm, and the volume fraction of TiBw in the composite powder is 5.1%.
[0031] Preferably, the drying of the composite powder in step 2 is carried out under vacuum conditions to prevent oxidation of the powder.
[0032] Preferably, in step 3, the surface pretreatment is as follows: the workpiece to be clad is cut to a desired size by wire cutting, and sandblasted to remove the surface oxide layer so that the surface is clean and smooth.
[0033] Preferably, the laser cladding process parameters in step 4 are: laser power: 1000-1500 W, scanning speed: 8-11 mm / s, spot diameter: 3 mm, powder feeding amount: 10 g / min, layer lifting: 0.8 mm, scanning spacing: 5 mm, and argon protection is used during the cladding process.
[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0035] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0036] Example 1 A method for preparing a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod comprises the following steps: Step 1: Select TC4-TiBw composite powder with a particle size of 45-150 μm and a volume fraction of 5.1% as raw material; Step 2: Place the composite powder in step 1 in a vacuum drying oven and dry for 6 hours at a vacuum degree of 0.08 MPa; Step 3: Using ATI425 titanium alloy as the substrate, perform sandblasting surface pretreatment on it; Step 4: The ATI425 titanium alloy after surface pretreatment is laser clad with TC4-TiB composite powder to prepare a titanium-based composite coating. The laser cladding equipment adopts a coaxial powder feeding method. The laser cladding process parameters are as follows: laser power: 1300W, scanning speed: 9mm / s, spot diameter: 3mm, powder feeding amount: 10g / min, layer lifting: 0.8mm, scanning spacing: 5mm, and argon protection is used during the cladding process; Step 5: Clean the welding slag and impurities on the surface of the cladding layer to obtain a titanium-based composite coating.
[0037] Example 2 A method for preparing a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod comprises the following steps: Step 1: Select TC4-TiBw composite powder with a particle size of 45-150 μm and a volume fraction of 5.1% as raw material; Step 2: Place the composite powder in step 1 in a vacuum drying oven and dry for 6 hours at a vacuum degree of 0.08 MPa; Step 3: Using ATI425 titanium alloy as the substrate, perform sandblasting surface pretreatment on it; Step 4: The ATI425 titanium alloy after surface pretreatment is laser clad with TC4-TiB composite powder to prepare a titanium-based composite coating. The laser cladding equipment adopts a coaxial powder feeding method. The laser cladding process parameters are as follows: laser power: 1500W, scanning speed: 9mm / s, spot diameter: 3mm, powder feeding amount: 10g / min, layer lifting: 0.8mm, scanning spacing: 5mm, and argon protection is used during the cladding process; Step 5: Clean the welding slag and impurities on the surface of the cladding layer to obtain a titanium-based composite coating.
[0038] Example 3 A method for preparing a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod comprises the following steps: Step 1: Select TC4-TiBw composite powder with a particle size of 45-150 μm and a volume fraction of 5.1% as raw material; Step 2: Place the composite powder in step 1 in a vacuum drying oven and dry for 6 hours at a vacuum degree of 0.08 MPa; Step 3: Using ATI425 titanium alloy as the substrate, perform sandblasting surface pretreatment on it; Step 4: The ATI425 titanium alloy after surface pretreatment is laser clad with TC4-TiB composite powder to prepare a titanium-based composite coating. The laser cladding equipment adopts a coaxial powder feeding method. The laser cladding process parameters are as follows: laser power: 1000W, scanning speed: 9mm / s, spot diameter: 3mm, powder feeding amount: 10g / min, layer lifting: 0.8mm, scanning spacing: 5mm, and argon protection is used during the cladding process; Step 5: Clean the welding slag and impurities on the surface of the cladding layer to obtain a titanium-based composite coating.
[0039] Example 4 A method for preparing a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod comprises the following steps: Step 1: Select TC4-TiBw composite powder with a particle size of 45-150 μm and a volume fraction of 1% as raw material; Step 2: Place the composite powder in step 1 in a vacuum drying oven and dry for 6 hours at a vacuum degree of 0.08 MPa; Step 3: Using ATI425 titanium alloy as the substrate, perform sandblasting surface pretreatment on it; Step 4: The ATI425 titanium alloy after surface pretreatment is laser clad with TC4-TiB composite powder to prepare a titanium-based composite coating. The laser cladding equipment adopts a coaxial powder feeding method. The laser cladding process parameters are as follows: laser power: 1500W, scanning speed: 9mm / s, spot diameter: 3mm, powder feeding amount: 10g / min, layer lifting: 0.8mm, scanning spacing: 5mm, and argon protection is used during the cladding process; Step 5: Clean the welding slag and impurities on the surface of the cladding layer to obtain a titanium-based composite coating.
[0040] Example 5 A method for preparing a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod comprises the following steps: Step 1: Select TC4-TiBw composite powder with a particle size of 45-150 μm and a volume fraction of 10% as raw material; Step 2: Place the composite powder in step 1 in a vacuum drying oven and dry for 6 hours at a vacuum degree of 0.08 MPa; Step 3: Using ATI425 titanium alloy as the substrate, perform sandblasting surface pretreatment on it; Step 4: The ATI425 titanium alloy after surface pretreatment is laser clad with TC4-TiB composite powder to prepare a titanium-based composite coating. The laser cladding equipment adopts a coaxial powder feeding method. The laser cladding process parameters are as follows: laser power: 1500W, scanning speed: 9mm / s, spot diameter: 3mm, powder feeding amount: 10g / min, layer lifting: 0.8mm, scanning spacing: 5mm, and argon protection is used during the cladding process; Step 5: Clean the welding slag and impurities on the surface of the cladding layer to obtain a titanium-based composite coating.
[0041] Example 6 A method for preparing a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod comprises the following steps: Step 1: Select TC4-TiC composite powder with a particle size of 45-150 μm and a volume fraction of 1% as raw material; Step 2: Place the composite powder in step 1 in a vacuum drying oven and dry for 6 hours at a vacuum degree of 0.08 MPa; Step 3: Using ATI425 titanium alloy as the substrate, perform sandblasting surface pretreatment on it; Step 4: The ATI425 titanium alloy after surface pretreatment is laser clad with TC4-TiC composite powder to prepare a titanium-based composite coating. The laser cladding equipment adopts a coaxial powder feeding method. The laser cladding process parameters are as follows: laser power: 1500W, scanning speed: 9mm / s, spot diameter: 3mm, powder feeding amount: 10g / min, layer lifting: 0.8mm, scanning spacing: 5mm, and argon protection is used during the cladding process; Step 5: Clean the welding slag and impurities on the surface of the cladding layer to obtain a titanium-based composite coating.
[0042] Example 7 A method for preparing a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod comprises the following steps: Step 1: Select TC4-TiC composite powder with a particle size of 45-150 μm and a volume fraction of 5.1% as raw material; Step 2: Place the composite powder in step 1 in a vacuum drying oven and dry for 6 hours at a vacuum degree of 0.08 MPa; Step 3: Using ATI425 titanium alloy as the substrate, perform sandblasting surface pretreatment on it; Step 4: The ATI425 titanium alloy after surface pretreatment is laser clad with TC4-TiC composite powder to prepare a titanium-based composite coating. The laser cladding equipment adopts a coaxial powder feeding method. The laser cladding process parameters are as follows: laser power: 1500W, scanning speed: 9mm / s, spot diameter: 3mm, powder feeding amount: 10g / min, layer lifting: 0.8mm, scanning spacing: 5mm, and argon protection is used during the cladding process; Step 5: Clean the welding slag and impurities on the surface of the cladding layer to obtain a titanium-based composite coating.
[0043] Example 8 A method for preparing a laser cladding titanium-based composite coating on the surface of a titanium alloy drill rod comprises the following steps: Step 1: Select TC4-TiC composite powder with a particle size of 45-150 μm and a volume fraction of 10% as raw material; Step 2: Place the composite powder in step 1 in a vacuum drying oven and dry for 6 hours at a vacuum degree of 0.08 MPa; Step 3: Using ATI425 titanium alloy as the substrate, perform sandblasting surface pretreatment on it; Step 4: The ATI425 titanium alloy after surface pretreatment is laser clad with TC4-TiC composite powder to prepare a titanium-based composite coating. The laser cladding equipment adopts a coaxial powder feeding method. The laser cladding process parameters are as follows: laser power: 1500W, scanning speed: 9mm / s, spot diameter: 3mm, powder feeding amount: 10g / min, layer lifting: 0.8mm, scanning spacing: 5mm, and argon protection is used during the cladding process; Step 5: Clean the welding slag and impurities on the surface of the cladding layer to obtain a titanium-based composite coating.
[0044] Microstructure morphology analysis and mechanical property test were performed on a titanium-based composite coating with a quasi-continuous network distribution of a nano-reinforced phase prepared by the present invention. The structure and properties of the titanium-based composite coating prepared by the present invention are as follows: Figure 1 The X-ray diffraction diagrams of the titanium-based composite coatings and cladding raw material powders prepared in Examples 1 and 2 of the present invention show that no impurity phase is generated in the cladding layer compared with the raw material powder.
[0045] Figure 2The scanning electron microscope images of the titanium-based composite coatings prepared in Examples 1 and 2 of the present invention show that the reinforcement phases are precipitated at the grain boundaries to form an obvious network structure.
[0046] Figure 3 This is a high-magnification scanning electron microscope image of the titanium-based composite coating prepared in Example 2 of the present invention. It can be seen from the image that the diameter of TiBw is nanometer-level.
[0047] Figure 4 The side scanning electron microscope images of the fracture surface of the titanium-based composite coating prepared in Example 1 and Example 2 of the present invention in the three-point bending test are shown in FIG. Figure 4 (a) is a side scanning photo of the three-point bending fracture of the titanium-based composite material prepared in Example 1. Figure 4 (b) is a side scanning photograph of the three-point bending fracture of the titanium-based composite material prepared in Example 2. It can be seen that neither of the two titanium-based composite materials broke at the junction, indicating that the two cladding layers have good metallurgical bonding with the substrate.
[0048] The present invention prepares a titanium-based composite coating with a nano-enhanced phase in a quasi-continuous network distribution on the surface of a low-cost titanium alloy ATI425, and the surface hardness and wear resistance are better than those of the substrate.
[0049] Figure 5 The microhardness and macrohardness test results of the titanium-based composite coatings prepared in Examples 1 and 2 of the present invention are as follows: Figure 5 (a) is the microhardness test results of the titanium-based composite materials and substrates prepared in Examples 1 and 2. Figure 5 (b) is the macro-hardness test result of the titanium-based composite materials and substrates prepared in Example 1 and Example 2. By comparison, it can be seen that the micro-hardness values of the cladding samples in the cladding depth direction show an overall decreasing distribution from the surface to the substrate. The macro-average hardness value of the cladding layer prepared in Example 1 is 350.33HV, the macro-average hardness value of the cladding layer prepared in Example 2 is 358.67HV, and the average macro-hardness value of the ATI425 alloy substrate is 296.67HV. Compared with the substrate, the macro-hardness of the cladding layers prepared in Example 1 and Example 2 increased by 19% and 21% respectively. The wear resistance of the titanium-based composite materials and substrates prepared in Example 1 and Example 2 was tested using a reciprocating testing machine with a load of 5N and 15N, a reciprocating distance of 3mm, a reciprocating time of 20min, a reciprocating number of 500t / m, and a ceramic ball (φ=5mm) as the friction pair. Figure 6 From the wear rate results, under loads of 5N and 15N, the wear amount of the cladding layers prepared in Examples 1 and 2 is smaller than that of the substrate, indicating that the wear resistance of the cladding layers is better than that of the substrate.
[0050] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a titanium-based composite coating by laser cladding on the surface of a titanium alloy drill rod, characterized in that: The following steps are involved: The surface of the pretreated titanium alloy drill pipe is subjected to laser cladding using spherical titanium-based composite powder as a raw material to form a titanium-based cladding layer on the surface of the titanium alloy drill pipe, and the titanium-based composite coating is obtained after cleaning impurities on the surface of the titanium-based cladding layer; The spherical titanium-based composite powder is a spherical TC4-TiBw composite powder or a spherical TC4-TiC composite powder.
2. The method for preparing a titanium-based composite coating by laser cladding on the surface of a titanium alloy drill rod according to claim 1, characterized in that: The spherical titanium-based composite powder is dried before use; the drying method is vacuum drying; the vacuum drying time is 4-6 hours, and the vacuum degree is 0.05 MPa-0.08 MPa.
3. The method for preparing a titanium-based composite coating by laser cladding on the surface of a titanium alloy drill rod according to claim 1, characterized in that: The method for preparing the pretreated titanium alloy drill rod is as follows: cutting the titanium alloy drill rod to a desired size by wire cutting, and performing sandblasting.
4. The method for preparing a titanium-based composite coating by laser cladding on the surface of a titanium alloy drill rod according to claim 1, characterized in that: The process parameters of the laser cladding are: laser power: 1000-1500W, scanning speed 8-11mm / s, spot diameter 3mm, powder feeding amount 10g / min, layer lifting 0.8mm, scanning spacing 5mm, and argon protection is used in the cladding process.
5. The method for preparing a titanium-based composite coating by laser cladding on the surface of a titanium alloy drill rod according to claim 1, characterized in that: The particle size of the spherical titanium-based composite powder is 45-150 μm.
6. The method for preparing a titanium-based composite coating by laser cladding on the surface of a titanium alloy drill rod according to claim 1, characterized in that: The volume fraction of the TiBw / TiC reinforcement phase in the spherical titanium-based composite powder is 1-6 wt.%.
7. The method for preparing a titanium-based composite coating by laser cladding on the surface of a titanium alloy drill rod according to claim 1, characterized in that: The volume fraction of the TiBw reinforcement phase in the spherical titanium-based composite powder is 5.1%.
8. The method for preparing a titanium-based composite coating by laser cladding on the surface of a titanium alloy drill rod according to claim 1, characterized in that: The material of the titanium alloy drill rod is ATI425 titanium alloy.
9. The method for preparing a titanium-based composite coating by laser cladding on the surface of a titanium alloy drill rod according to claim 1, characterized in that: The powder feeding method of the laser cladding is coaxial powder feeding.
10. A laser cladding titanium-based composite coating on the surface of a titanium alloy drill pipe, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method and application of particle-reinforced titanium-based composite powder
CN116532644A
Preparation method of composite ceramic particle reinforced titanium alloy wear-resistant coating
CN116987922A
Heterostructure titanium-based composite material with nano reinforced phase and preparation method of heterostructure titanium-based composite material
CN119082546A